INSTITUTIONAL ENTREPRENEURSHIP IN EMERGING FIELDS: HIV/AIDS TREATMENT ADVOCACY IN CANADA. - Maguire, S.; Hardy, C.; Lawrence, T. B. (Academy of Management Journal, 2004)
In a qualitative study of the emerging field of HIV/AIDS treatment advocacy in Canada, we found that institutional entrepreneurship involved three sets of critical activities: (1) the occupation of “subject positions” that have wide legitimacy and bridge diverse stakeholders, (2) the theorization of new practices through discursive and political means, and (3) the institutionalization of these new practices by connecting them to stakeholders’ routines and values.